Indigenous knowledge and local practices for disaster risk reduction: A study of Kailali district - Timilsena, Narayan Prasad; Devkota, Krishna Maya (Geographical Journal of Nepal, 2022)
Disasters which are resulted due to the natural or anthropogenic environmental damage processes such as deforestation, desertification, loss of biodiversity, soil erosion etc. and are increasing day by day. As such there are potentialities for outbreaks and their high risk at any places at any time. There are many literatures which suggest the possibility of disaster risk reduction and early warning through local indigenous knowledge and practices. The present study is an attempt to explore, evaluate andanalyse the local knowledge and skills that are being practiced and used to reduce the risk of various types of natural hazards. Kailali district lying in the Sudur Paschim Province of Nepal is chosen as the study area. Chure rural municipality lying within Hill areas and Tikapur urban municipality lying within Terai plain areas of the district were selected as the research sites to evaluate the landslide and flood related local indigenous knowledge and practices respectively. Using a multi-assessment methodology of collecting information through targeted group discussions, key informant interviews, household surveys, and field observation methods, an attempt has been made to analyse the data to explore indigenous local knowledge, skills, and traditional practices related to disaster risk and mitigation in the study area. The indigenous knowledge, skills and practices on disaster risk reduction and early warning system have been developed by generations and tested in the absence of the scientific developments. However, many communities have lost their local knowledge, skills, and traditional practices because of non transfer by the senior citizens to the young generations. The findings of the study indicate that indigenous and local knowledge and practices are valuable resources that can support in the process of disaster management, prevention, preparedness, and cost-effective disaster risk reduction. Therefore, the researchers view that it would be wise decision focusing the policy framework by integrating indigenous and local knowledge, wisdom, and skills of the local people.